Konsumen Perbankan Oleh Otoritas Jasa Keuangan dan Perlindungan Hukumnya - Assegaf, Ahmad Jamal (UNES Law Review, 2023)
The globalization of the financial system, significant advancements in the field of information technology, and innovations in the financial sector have all contributed to the creation of a financial system that is sophisticated, dynamic, and interconnected in terms of the products and institutions found across the various financial subsectors. Concerns for the Financial Services Authority include integrated supervision of the financial services industry (conglomerate), consistent consumer protection policies across the entirety of the financial services sector, acts that represent moral hazard, and suboptimal consumer protection in the financial services industry. Consumer protection in the financial services sector aims to create a reliable consumer protection system, increase consumer empowerment, and raise financial service business actors' awareness of the significance of protection in order to increase public confidence in the financial services sector. This is done in order to increase the amount of money that people put their trust in the financial services sector to earn. The establishment of consumer protection legislation is of the utmost importance. This is in compliance with the existing legislation for the purpose of avoiding potential complications in the future created by the fact that everyone, either individually or collectively, will ultimately become a customer for a certain product or service.